MEMAHAMI KOMUNIKASI KELOMPOK DALAM PENDAMPINGAN KORBAN KEKE.RASAN BERBASIS JENDER - Yuliyanto Budi Setiawan (JURNAL ILMU SOSIAL, 2006)
Through this study, some topics which were ever communicated by participants together in a meeting of Support Group, examples violence cases expe-rienced by each member, and the form of gender emancipation. The process of com-munication taking place in the Support Group has resulted in producing members who are able to overcome their problem. One of the results can be detected from the members' attitude, when communicating in the forum, namely dare to tell their problems. Essentially, the success of realizing a therapy in group depended on the communication competence and the commitment having to be possessed by those discussion participants.